Students’ Perceptions on Using Zoom Application in Debate Course during Crisis Remote Teaching - Fatoni, Mohammad (English Department, Universitas Negeri Surabaya, 2021)
This research aims to know the students' perception of using zoom application in a debate course during crisis remote teaching. The government of Indonesia gave an order to the Higher Education Commission, asked them to start preparing for crisis remote teaching via online learning modes, rescheduled all of the exams given, and helped the students online learning until the COVID-19 crisis remained unchanged. Online learning is the leading choice for instruction within the middle of the Covid-19 flare-up. In Indonesia, not all students are commonplace with the online learning framework, so this has become a new thing that requires adjustment. The research design used is mix method in this research. There are 26 university students who participate in this research. This research was presented quantitatively and descriptively to reveal the students' perceptions and difficulties comprehensively. The research finds ZOOM Application gets a positive perception because it is effective and comfortable. However, the problems that the students face are the device to do online learning and internet connection. It is suggested that zoom app is still appropriate to be used in debate course class due to many advantages than the problems that emerge during crisis remote teaching.